Potato (Solanum tuberosum) for sustaining food and nutrition security in developing world - Pandey, S K; Singh, S V; Sarkar, D (The Indian Journal of Agricultural Sciences, 2005)
Potato (Solanum tuberosum L.) is one of the most important food crops after wheat (Triticum aestivum: emend. Fiori & Paol.), maize (Zea mays L.) and rice ( Oryza sativa L.), historically contributing to food and nutrition security in the world. This tuber crop exists with more than 200 wild species. The cultivated potatoes are tetraploid (2n=4x=48), display complex tetrasomic inheritance and are propagated asexually through tubers. Tuberization is a complex physiological process occurred on underground stolons under the influence of both extrinsic as well as intrinsic factors. The fascinating reproductive biology characterized by 2n gametes and endosperm balance number concept allows introgression of traits from wild to cultivated potato species, and the transgenic approach has further expanded the scope for selective introgression orgenes across the trans-specific and/ or trans-generic barriers. Late blight [Phytophthora infestans (Mont) de Bary] is the most severe disease that threats the potato crop worldwide, and next to severity are the systematic viral diseases, which cause rapid degeneration of seeds. Therefore, the availability of healthy seeds comprises the most important aspect for potato production, and recent biotechnological approaches have been successfully integrated into disease-free seedproduction scheme. In India, more than 80% of potatoes are grown in sub-tropical plains under conditions distinct from Europe, and this has only been possible through concerted research at the Central Potato Research Institute, Shimla, over the past 55 years resulting in the development of 35 high-yielding potato varieties for diverse agro-climatic conditions and the innovation of seed plot technique for augmenting the seed production. India now ranks number three both in area and production of potato in the world, and is poised to achieve the maximum annual growth rate in the coming decade. Coincident with neo-liberalization and rapid urbanization, a growing synergy between private and public sector investment in processing industry is all set to sustain and diversify potato production in the country in the 21st century for securing the food and nutrition.